JARINGAN SOSIAL DALAM AKTIVITAS PEDAGANG KUE TRADISIONAL DI KELURAHANLIMBUNGAN BARU KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Agusti, Muhammad Sandy; Yusuf, Yusmar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Limbungan Baru Village, Rumbai Pesisir Sub District, Pekanbaru City. The purpose of this study is to find out what social network contained in the activity of snack merchants and how the characteristics of traders in utilizing this field of business maximally, and how the influence of the network on product availability. Purposive Sampling sampling technique because the author has set some criteria of the subject that will be used as a source of information in research that will be done as many as 14 people. The author uses Qualitative methods with data collection techniques of observation, interviews, documentation and literature study. The type of research conducted by the authors is descriptive qualitative research. The results from the field said that the characteristic of a merchants traditional cake with snack craftsmen in Limbungan Baru Village, District of Rumbai Pesisir Pekanbaru City can be seen from Age, Education, Ethnic, Religion, Cake, and Source of Capital. The type of social network created on social networks in the activity of merchants traditional cake is a network of interests in which this network is formed due to an element of interest in forming such a network. Social capital further emphasizes the potential of groups and between groups with an attention space on social networks, norms, values, and trust among people.The Key word: Social Networks, Traders, Social Capital